PENGARUH TERPAAN BERITA DAN KUALITAS INFORMASI TERHADAP FOLLOWERS AKUN TIKTOK @METRO_TV DALAM BERITA PEMBUNUHAN BRIGADIR JOSHUA. - Didan Galih Muhammad Yusuh, (2023)
The high number of internet service users in Indonesia based on We Are Social research in 2023 is 204.7 million or around 73.7% of Indonesia's population are internet users. With the fact that the main reason people in Indonesia use the internet in 2023 is that as many as 80.1% use the internet to find information on social media. This phenomenon prompted researchers to examine the effect of news exposure and the quality of information on the satisfaction of followers of the Tiktok @metro_tv account in the news of Brigadier Joshua's murder through the uses gratification theory. This study aims to identify and explain the effect of news exposure and information quality on the satisfaction of followers of the Tiktok @metro_tv account in news of the murder of Brigadier Joshua. The theory used in this study uses the uses and gratification theory with quantitative research methods. The population in this study is followers of the Tiktok @metro_tv account, which totals 4,700,000 followers with a sample count of 400 respondents taken using the Slovin formula. The results of the study concluded that news exposure and quality of information partially affect the satisfaction of the followers of the @metro_tv tiktok account in the News of the Murder of Brigadier Joshua with a large influence of 74.4% and the remaining 25.6% is influenced by variables outside of the research variables.